The Queerness of the Man-Child - Lance Weldy (Barnboken: Tidskrift för Barnlitteraturforskning, 2021)
The literary man-child character can function as a subversive agent within the text to expose traditional ideologies and suggest alternate possibilities. Much beloved in Sweden, Karlson from Astrid Lindgren’s Karlson on the Roof trilogy (1955–1968) represents this kind of man-child character in texts for children, particularly through his queerness. The trilogy illuminates Karlson’s queerness by contrasting him with the normative reality of 20th-century Stockholm through his trademark narcissism, primal desires, and illogical or fallacious rhetoric that often invokes silence from children and adults within the story. Through the lens of Jack Halberstam’s queer subcultures, Karlson can be appreciated as a specific kind of literary man-child character that necessitates a legitimated queer visibility. This visibility is cultivated by his non-normative belief system and buttressed by his resistance to being silenced or kept secret from this normative world. Furthermore, Karlson’s queerness fuels his charisma, making him popular because of his behaviour, not despite it. Ultimately, his queerness as a man-child character disrupts traditional boundaries and delineations of the child/adult binary and allows the child reader to witness the vulnerabilities of normative institutions while also appreciating diversity in non-normative family structures.